Safety of Drug-Eluting-Beads Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma in Patients with Transjugular Intrahepatic Portosystemic Shunt - Rief, Katherine; Pirasteh, Ali; Shenoy-Bhangl, Anuradha; Ganguli, Suvranu; Kalva, Sanjeeva P. (Journal of Clinical Interventional Radiology ISVIR, 2018)
Purpose To assess the safety of drug-eluting beads transarterial chemoembolization (DEB-TACE) for unresectable hepatocellular carcinoma (HCC) in patients with transjugular intrahepatic portosystemic shunt (TIPS).Materials and Methods Records of patients with a patent TIPS who underwent DEB-TACE for inoperable HCC from 2005 to 2014 at two institutions were reviewed. Patient demographics, number of procedures, extent of embolization (lobar vs. segmental), 30-day mortality, and postprocedure adverse events classified based on Common Terminology Criteria for Adverse Events (CTCAE V4.03) were recorded.Results From the total of 10 patients included (6 male, average age: 59), 3 were classified as Child A and 7 as B. Tumor Barcelona clinic liver cancer (BCLC) stage was A in three patients, B in six, and C in one. Patients underwent doxorubicin DEB-TACE with a median dose of 100 mg (range: 50–100). Number of TACE procedures per patient ranged from 1 to 4 (median: 1). Three (30%) patients experienced toxicity grade 2 or higher immediately following the procedure. One patient had grade 3 toxicity of aspartate transaminase (AST), alanine transaminase (ALT), and bilirubin. Three patients had extended hospital stays beyond 48 hours due to adverse events, including edema, acute pancreatitis, and a hepatic abscess discovered a week after the procedure. All 10 patients were alive and discharged from the hospital at 30 days after the procedure.Conclusion DEB-TACE can be well tolerated by patients with a patent TIPS, given adequate liver function. Lobar DEB-TACE is associated with higher risk of complications.
Keywords: transarterial chemoembolization; hepatocellular carcinoma; transjugular intrahepatic portosystemic shunt